The Allure of Free Tuition - Douglass, John (International Higher Education, 2020)
Throughout the world, tuition at any level is regarded as a significant barrier for university access to disadvantaged socioeconomic groups. In the United States, student debt levels are at an historic high. In most cases, the political movement for free tuition does not provide any significant plan on how to make up lost revenue. Consolidating existing financial aid sources, combined with progressive tuition levels, may be a promising model.